THE DYNAMICS OF CENTRALISM BEHIND THE CLOAK OF AUTONOMY: A CRITICAL REVIEW OF THE LEGAL PHILOSOPHY OF THE IMPLEMENTATION OF LOCAL GOVERNMENT - Hendro Tri Subiyantoro; Afdhal Mahatta (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2026)
Indonesia's regional self-governance, launched post-1998 reformasi, rests on subsidiarity and decentralization as core tenets of local administration. Yet, emergent realities expose a stark contradiction between nominal affirmation of provincial sovereignty and pervasive curbs imposed via regulatory frameworks. Utilizing a normative juridical methodology featuring systematic and purposive hermeneutics, this inquiry dissects disparities between statutory designs of autonomy and practical execution. Outcomes reveal that Law No. 1 of 2022 on Inter-Governmental Fiscal Ties fosters financial reliance undermining provincial self-determination, whereas Law No. 3 of 2022 on the New Capital City imposes administrative structures bypassing local democratic norms. Together with tacit recentralizing devices, these enactments engender a facade of autonomy, granting procedural leeway amid substantive curtailment. Imperative juridical realignment of local governance philosophy demands bolstering subsidiarity, overhauling fiscal linkages, and reorienting central-local dynamics toward equitable, partnership-oriented distributive justice.